Analisis Hukum Islam Terhadap Praktik Pengelolaan Zakat Fitrah Di Desa Padaelo Kec. Mattiro Bulu Kab. Pinrang: Islamic Legal Analysis of the Practice of Zakat Fitrah Management in Padaelo Village, Mattiro Bulu District, Pinrang Regency - Munira; Nabila al Azizah; Nur Afifah Syafruddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
In Indonesia, its management has not been fully aligned with Islamic legal principles, with certain long-standing local traditions still influencing practice. This study examines the management of zakat fitrah in Padaelo Village, Mattiro Bulu District, Pinrang Regency, from an Islamic legal perspective. Using qualitative field research with normative (doctrinal) and sociological approaches, the number of informants is 10 people, the study finds that the local community understands the obligation of zakat fitrah, its rightful recipients, and the parties responsible for payment. Payments are made in rice or cash equivalent to the price of rice, although most scholars consider monetary substitution impermissible. Zakat administration is handled by mosque imams and Qur’an teachers. Overall, the management is largely consistent with Islamic law, though certain aspects require improvement. This research aims to enhance public awareness and serve as a reference for further studies on zakat management in rural Indonesia.